Private Participation in Telecommunications : Recent Trends - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
More than ninety developing economies opened their telecommunications sector to private participation between 1990 and 1998. These countries transferred to the private sector the operating or construction risk, or both, of more than 500 projects, attracting investment commitments of US$214 billion. Two-thirds of that amount has been invested in expanding and modernizing networks; the other third has gone to governments as divestiture revenues or license fees. The investment shows three main trends: Latin America is in the lead. Private participation takes place in increasingly competitive market structures. And divestitures and greenfield projects outnumber operations and management contracts.